ANALISIS EFEKTIVITAS PENETAPAN JALUR TERKAIT DENGAN DWELLING TIME DI KANTOR PELAYANAN UTAMA BEA DAN CUKAI TIPE A TANJUNG PRIOK - Sunarmin Sunarmin; Noviandari Sari Utami; Wiwin Eka Yulianita (Jurnal Pajak Vokasi (JUPASI), 2019)
Path determination is one of the customs procedures regulated in Law No. 17 of 2006 on customs. Considering the Directorate General of Customs and Excise, especially Tanjung Priok Customs and Excise KPU is faced with two functions, namely service and supervision, the strategic step taken to answer the problems of both functions is by determining the path. This study aims to discuss the determination of paths associated with dwelling time. The main problem in this research is the extent of the effectiveness of the application of the determination of the path and its relation to the dwelling time which is the loading and unloading time of the container carried from the vessel to the container out of the port. This research is a qualitative descriptive research with data collection techniques in the form of interviews and data secondary. From the results of interviews and data processed by the authors then concluded that with the establishment of a system of determining the path at the Tanjung Priok Customs and Excise KPU has been quite effective in reducing the dwelling time in the port of Tanjung Priok.